Hungarian Monitoring, 9 November 1988 . [Magyar rádiófigyelő], 1988. november 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - George Bush will be the 41st US president, reports - On Bush's press conference - How does Moscow view the new American president? - Reports from London, Brussels and Stockholm - Leader of Bonn chancellor's office travels to the GDR - Roundtable discussions held in Slovakia on Gabčíkovo-Nagymaros dam construction Domestic Affairs: - Károly Grósz receives Italian vice-president of the council, Gianni de Michelis - Party general secretary gives interview to Le Monde on reforms currently taking shape - G. Gherasimov in Hungary at East-West relations conference - Bible published in graphic novel format by French publisher Larousse and Fabula press in Hungary: an authentic version of biblical texts finally readable for children Economy: - Factory directors: producers or entrepreneurs can already trade abroad as an individual right Külpolitika: - George Bush lesz az Egyesült Államok 41. elnöke, tudósítások - Bush sajtóértekezletéről - Hogyan tekint Moszkva az új amerikai elnökre? - Londoni, brüsszeli és stockholmi tudósítások - A bonni kancellári hivatal vezetője az NDK-ba utazik - Kerekasztal beszélgetést tartottak Szlovákiában a Bős-nagymarosi vízlépcső építéséről Belpolitika: - Grósz Károly fogadta az olasz kormány elnökhelyettesét, Gianni de Michelist - A párt főtitkára interjút adott a LE MONDE-nak a jelenleg kibontakozó reformokról - G. Geraszimov Magyarországon tartózkodik a Kelet-nyugati kapcsolatok konferenciáján - Képregény formájában jelentette meg a Bibliát a francia Larousse és a magyar Fabula kiadó - Hiteles bibliai szöveget olvashatnak végre a gyerekek Gazdaság: - IPARGAZDÁK: ma már alanyi jogon is kereskedhet külpiacon a termelő vagy vállalkozó